Epigenetic Factors and Mitochondrial Biology in Yeast: A New Paradigm for the Study of Cancer Metabolism? - Stoppacciaro, Antonella; Di Vito, Serena; Filetici, Patrizia (Frontiers in Pharmacology, 2018)
Bidirectional cross-talk between nuclear and mitochondrial DNA is fundamental for cell homeostasis. Epigenetic mechanisms regulate the inter-organelle communication between nucleus and mitochondria. Recent research highlights not only the retrograde activation of nuclear gene transcription in case of mitochondria dysfunction, but also the role of post-translational modifications of mitochondrial proteins in respiratory metabolism. Here we discuss some aspects and novel findings in S.cerevisiae. In yeast, KAT-Gcn5 and DUB-Ubp8 have a role in respiration and are localized, as single proteins, into mitochondria. These findings, beside the canonical and widely known nuclear activity of SAGA complex in chromatin regulation, provide novel clues on promising aspects linking evolutionary conserved epigenetic factors to the re-programmed metabolism of cancer cells.